Methamphetamine Use and Cardiovascular Disease: In Search of Answers. Issue 9 (September 2019) - Kevil, Christopher G.; Goeders, Nicholas E.; Woolard, Matthew D.; Bhuiyan, Md. Shenuarin; Dominic, Paari; Kolluru, Gopi K.; Arnold, Connie L.; Traylor, James G.; Orr, A. Wayne
Abstract : While the opioid epidemic has garnered significant attention, the use of methamphetamines is growing worldwide independent of wealth or region. Following overdose and accidents, the leading cause of death in methamphetamine users is cardiovascular disease, because of significant effects of methamphetamine on vasoconstriction, pulmonary hypertension, atherosclerotic plaque formation, cardiac arrhythmias, and cardiomyopathy. In this review, we examine the current literature on methamphetamine-induced changes in cardiovascular health, discuss the potential mechanisms regulating these varied effects, and highlight our deficiencies in understanding how to treat methamphetamine-associated cardiovascular dysfunction.